2002
DOI: 10.1051/apido:2002015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of honeybee peptide active against Paenibacillus larvae larvae through bacterial growth-inhibition assay on polyacrylamide gel

Abstract: -The inhibition bands showing activity against Gram-positive bacteria were detected by analyses of acidic extracts of honeybee heads, thoraxes, and royal jellies (RJs) using a bacterial growth-inhibition assay on polyacrylamide gel. The presence of antibacterial peptide royalisin and another unknown peptide was found in two detected RJ inhibition bands by N-terminal sequencing. The data suggested that royalisin was the peptide responsible for the activity against Paenibacillus larvae larvae and other tested Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 19 publications
2
47
0
5
Order By: Relevance
“…Two isolated proteins (major royal jelly protein 2 and defensin-1) and the fatty acid 10-hydroxy-2-decenoic acid are discussed as candidates of the antimicrobial activity of royal jelly (Bachanová et al 2002;Bíliková et al 2001Bíliková et al , 2009Chu et al 1992;Hornitzky 1998). The antimicrobial activity of royal jelly is not just dose dependent but also varies significantly among honeybee colonies (Rose and Briggs 1969).…”
Section: Food Jellymentioning
confidence: 99%
See 1 more Smart Citation
“…Two isolated proteins (major royal jelly protein 2 and defensin-1) and the fatty acid 10-hydroxy-2-decenoic acid are discussed as candidates of the antimicrobial activity of royal jelly (Bachanová et al 2002;Bíliková et al 2001Bíliková et al , 2009Chu et al 1992;Hornitzky 1998). The antimicrobial activity of royal jelly is not just dose dependent but also varies significantly among honeybee colonies (Rose and Briggs 1969).…”
Section: Food Jellymentioning
confidence: 99%
“…Honeybees may be able to adjust the quality of royal jelly in response to pathogen infections. Workers of P. larvae -infected colonies produce royal jelly with much higher amounts of antibacterial peptides (Bachanová et al 2002). Most likely, the combination of high-quality proteinous food, enhancing bee health, with increasing antimicrobial activity offers a simple and effective method for reducing or eliminating intra-colony P. larvae titres.…”
Section: Food Jellymentioning
confidence: 99%
“…It corresponds to 2.57 and 2.31-fold differences in relative amount of defensin1 normalized to TP and WSP, respectively (Table 1, samples 1-10). Among the tested samples were also RJs whose antimicrobial activity against P. larvae was previously determined by a bacterial inhibition assay on an acidic polyacrylamide gel (Bachanová et al 2002). We found that RJs that contained the highest amounts of defensin1 (samples 4 and 8) yielded also the strongest inhibition bands in the inhibition assay and vice versa those with lowest defensin1 amounts (samples 6 and 10) yielded the weakest inhibition bands.…”
Section: Study Of Expression Of Lj Defensin1 In Colonies and Factors mentioning
confidence: 84%
“…Besides defense mechanisms mentioned above, the diet of honeybee larvae-the larval jelly (LJ) has a potential to participate in protection against P. larvae infection (Rose & Briggs 1969;Hornitzky 1998;Bí-liková et al 2001;Bachanová et al 2002). Several proteinaceous and non-proteinaceous antimicrobial substances have been found in royal jelly (RJ), the diet of queen larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation